An Efficacy Comparison of Two Hemostatic Agents in a Porcine Liver Bleeding Model: Gelatin/Thrombin Flowable Matrix versus Collagen/Thrombin Powder - Paul Slezak; Claudia Keibl; Heinz Redl; Dirk Labahn; Heinz Gulle (Journal of Investigative Surgery, 2020)
Purpose: Management of bleeding during surgery can be aided by the application of topical hemostatic agents. This study compared the hemostatic efficacy of a new powder agent containing collagen, chondroitin sulfate, and thrombin (PCCT) with a flowable gelatin-thrombin matrix with smooth particles (SmGM) in a porcine liver bleeding model. Materials and Methods: Lesions 4–6 mm deep and ∼10 mm in diameter were created in porcine livers and treated with either SmGM or PCCT. Bleeding rate and grade were quantified before and 3, 7, and 11 minutes after treatment. Results: Thirty-two lesions each were treated with SmGM or PCCT; the median (Q1, Q3) initial bleeding rate was comparable between the two groups (8.43 [6.18, 10.68] g/min and 7.15 [5.16, 9.63] g/min, respectively). The residual bleeding rate was significantly lower at all time-points post treatment for SmGM compared with PCCT (3 minutes: 0.14 [0.07, 0.21] versus 0.46 [0.20, 1.20] g/min, p < 0.0001; 7 minutes: 0.07 [0.04, 0.11] versus 0.12 [0.08, 0.39] g/min, p = 0.001; 11 minutes: 0.05 [0.03, 0.08] versus 0.07 [0.05, 0.12] g/min, p = 0.043). Bleeding grade at 3 minutes was also significantly lower for SmGM compared with PCCT (median [Q1, Q3] 0.0 [0.0, 0.0] versus 1.0 [1.0, 2.0], p < 0.0001). PCCT required reapplication in approximately one-third of applications due to insufficient hemostasis 4 minutes after initial application and showed a tendency to stick to the wet gauze during approximation. Conclusions: In this bleeding model, treatment with SmGM resulted in reduced blood loss, no need for reapplication and was easier to apply compared with PCCT.